2013
DOI: 10.1136/bcr-2013-010220
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia and parkinsonism as a sequelae of typhoid fever: a rare experience

Abstract: Although neurological manifestations of typhoid fever was thought to be obsolete from modern world, emergence of multidrug resistant typhoid bacilli and reporting of outbreak of typhoid fever with a range of early neuropsychiatric manifestations from various parts of world has led clinicians and investigators to re-evaluate the clinical spectrum of this endemic sinister disease. An 18-year-old male student was admitted in psychiatry ward with mutism, staring look, posturing and rigidity. There was history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…Typhoid fever is commonly characterized by headache, stomach pain and a sustained high fever. In rare cases, typhoid fever patients have been found to exhibit neurological abnormalities (Dewan et al, 2009 ; Joshi et al, 2011 ; Szabo et al, 2013 ; Talukdar et al, 2013 ). A very high mortality rate, more so in infants, is associated with Salmonella infections of the brain (Drevets et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typhoid fever is commonly characterized by headache, stomach pain and a sustained high fever. In rare cases, typhoid fever patients have been found to exhibit neurological abnormalities (Dewan et al, 2009 ; Joshi et al, 2011 ; Szabo et al, 2013 ; Talukdar et al, 2013 ). A very high mortality rate, more so in infants, is associated with Salmonella infections of the brain (Drevets et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported various features from MRI investigation, ranging from normal appearance, demyelinating changes, symmetrical diffuse abnormal signal with central area of restricted diffusion to diffuse cerebral oedema (10)(11)(12)(13). The literature on imaging findings of Parkinsonism is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on imaging findings of Parkinsonism is lacking. Talukdar et al reported a normal appearance on MRI in a patient with catatonia and Parkinsonism (13), however, the MRI was done prior to the onset of Parkinsonism. To the best of our knowledge, this is the first case report demonstrating the MRI findings in a patient with typhoid fever and Parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… relapse (14 days up to 3 months following treatment) [ 4 ]; psychiatric disorders [ 20 ]; neurologic disorders [ 21 ], [ 22 ], [ 23 ]; ophthalmologic disorders [ 24 ]; intracranial abscess (47 years following typhoid fever) [ 25 ]; atrophic rhinitis [ 26 ]. …”
Section: Introductionmentioning
confidence: 99%